The Effect of Leadership Style and Work Discipline on the Performance of Avsec Officers at Sultan Muhammad Salahuddin Bima Airport - Ayu Indriyani; Arif Fakhrudin (CV. Rayyan Dwi Bharata, 2023)
Leadership style is a way to improve work discipline towards follower performance more than just transactional. With this leadership, officers can feel admiration, trust, and respect for the leader to do more than what is expected. Therefore, the work discipline factor must be considered by a company, because performance is the result of work in quality and quantity achieved by an officer in the achievement of carrying out tasks according to the responsibilities given to him. The purpose of this study (1) To determine the effect of leadership style on the performance of Avsec officers, (2) To determine the effect of work discipline on the performance of Avsec officers, (3) To determine the effect of leadership style and work discipline on the performance of Avsec officers at Sultan Muhammad Salahuddin Airport in Bima. This research was conducted in August and September 2022 using quantitative methods with saturated sampling techniques on 43 respondents of Avsec unit officers at Muhammad Salahuddin Bima Airport. Analysis using multiple linear regression tests, t tests, f tests, coefficient of determination (R2) tests. The results showed that (1) Leadership style has no significant effect on the performance of Avsec officers, (2) Work discipline has a significant effect on the performance of Avsec officers, (3) Leadership style and work discipline have a positive and significant effect on the performance of Avsec officers at Sultan Muhammad Salahuddin Airport Bima. In this case, the variable of leadership style and work discipline on officers is 70.8% and the remaining 29.2% is influenced by variables outside the variable model in this study.